Cultural Negotiation through Food - Wiratri, Amorisa (Kawalu: Journal of Local Culture, 2017)
Food is one of the common ways for one culture to penetrate an-other culture through migrants. Chinese migrants in Indonesia have in-troduced their food culture to Indonesians for some centuries and now Indonesians might find it difficult to recognize whether they are now lo-cal, fusion or Chinese food. The acceptance of Chinese food in Indonesia serves an example on how soft diplomacy and culture negotiation has completely succeeded. Chinese food has already blended with Indonesian culture and Indonesians nowadays are acquainted with. This study will use literature as main resources. Historical and anthropological approach will be used in analyzing the data. This paper tries to focus on three mains issues, which are the history of Chinese migration in Indonesia, the his-tory and acculturation of Chinese food in Indonesia and culture nego-tiation through food. In conclusion, the acceptance of Chinese food in Indonesia culture is part of the success of soft diplomacy and culture negotiation between Chinese migrants and Indonesian leads to the per-mission of other form of diplomacy.Keywords: Chinese, cultural negotiation, soft diplomacy, food